Pembangunan semula lapangan terbang Sultan Abdul Aziz Shah Subang / Muhammad Dzulkifli Sulaiman - Sulaiman, Muhammad Dzulkifli (2001)
The newly open Malaysia’s international airport on November 1998 has bring a new faces and history in Malaysia transportation. The spectacular fireworks and lights during the opening ceremony has shown Malaysia high commitment towards becoming a develop nation by the year 2020. With the combination of science and arts in its building design and planning, Kuala Lumpur International Airport (KLIA) will surely open the eyes of other countries to follow Malaysia footsteps in developing the transport industry. However, at the same time, with the opening of KLIA, it is also mean the end of Sultan Salahuddin Abd. Aziz Shah Airport (LTSAAS) in Subang as Malaysia international airport. For more than three decade, LTSAAS has shown a great ‘job’ in fulfilling government agenda. From a land filled with rubber plantation with some small holder taking some effort of the land, it has change into an ‘airport city’ with all kind of people from around the world, from businessman to tourist, walking and passing along before go to the next destination. It was surely a time of prosperity and wealth to the people of Subang. A lot of job opportunity was created and Subang itself has turn rapidly into a big town. However, with the closing of LTSAAS, a lot of people getting worried of what is going to happen to LTSAAS. The government realises of this feeling and for that a redevelopment of LTSAAS is necessary so it will bring back the glory of LTSAAS like it once was. But, before that, a thorough study should be done first so that the best decision can be make for redevelopment of LTSAAS. To achieve that, the decision must based on facts and detail assumption. When every information has put into places, only then it is implement. A thorough study is very important before we can pursue our objective especially if it involve big decision such as the redevelopment of LTSAAS. Hopefully, in the end everyone will get the profit from the redevelopment of LTSAAS.